Project-Based Learning for Integrated Arabic Language Skills: A Library-Based Review of Linguistic and Communicative Competence Development - Dewi Qotrun Nada Najwa; M. Miftahurrizkil Khairi; Adi Fadli (Dzil Majaz: Journal of Arabic Literature, 2026)
The integration of listening, speaking, reading, and writing remains a major challenge in Arabic language instruction, as these skills are often taught separately, resulting in limited communicative competence among learners. Although Project-Based Learning (PjBL) has been widely implemented in language education, comprehensive evidence regarding its role in integrating the four Arabic language skills is still limited. Therefore, this study aims to examine how PjBL facilitates the integrated development of Arabic language skills while fostering learners’ linguistic and communicative competence. This study employed a qualitative library research approach by analyzing peer-reviewed journal articles, books, and relevant academic publications published between 2021 and 2025. Data were collected through documentation and analyzed using content analysis to identify recurring themes, instructional patterns, and pedagogical implications. The findings reveal that PjBL creates a student-centered learning environment in which listening, speaking, reading, and writing are developed simultaneously through interconnected project stages, including planning, information gathering, collaborative discussion, product development, presentation, and reflection. Listening skills are enhanced through exposure to instructions and authentic audio materials, speaking through group discussions and presentations, reading through the exploration of various written sources, and writing through the production of reports, dialogues, posters, and digital content. Furthermore, PjBL promotes learner motivation, creativity, critical thinking, collaboration, self-confidence, and meaningful language use in authentic contexts. Despite challenges related to instructional time, teacher readiness, and technological resources, the findings suggest that PjBL remains an effective pedagogical approach for developing integrated Arabic language proficiency. This study contributes a comprehensive synthesis of recent evidence and offers a conceptual framework for implementing integrated, communicative, and project-oriented Arabic language instruction in secondary education.